Application of SMOTE in Sentiment Analysis of MyXL User Reviews on Google Play Store - Chamidy, Totok; Badriyah, Badriyah; Suhartono, Suhartono (UIN Sunan Kalijaga Yogyakarta, 2025)
Texts that express customer opinions about a product are important input for companies. Companies obtain valuable information from consumer perceptions of marketed products by conducting sentiment analysis. However, real-world text datasets are often unbalanced, causing the prediction results of classification algorithms to be biased towards the majority class and ignoring the minority class. This study analyzes the sentiment of MyXL user reviews on the Google Play Store by comparing the performance of the Logistic Regression and Support Vector Machine algorithms in the SMOTE implementation. This analysis uses TF-IDF to extract features and GridSearchCV to optimize the accuracy, precision, recall, and F1-score evaluation metrics. This study follows several scenarios of dividing training data and test data. SVM implementing SMOTE is the algorithm with the best performance using the division of training data (90%) and test data (10%), resulting in accuracy (73.00%), precision (67.13%), recall (65.82%), and F1-score (66.30%).